Avaliação dos níveis de radônio no Campus Caçapava do Sul da Universidade Federal do Pampa - Brum, Fernanda Nicolodi (2021)
Radon (Rn²²²) is a naturally occurring noble gas that emits alpha particles, thus having radioactive and potentially carcinogenic activity. In the United States and throughout the European Community, there is great concern to avoid the risks that radon can bring to public health, mainly due to occupational and residential exposure. Despite the evidence relating to exposure to radon, there is no specific regulated recommendation in Brazil for controlling exposure to radon, even though it is a country with great potential for mineral extraction and large reserves of uranium, from which radon is generated. Specifically in the region of Caçapava do Sul, the geological formation on which the city is located is a granitic formation, which has a strong relationship with high levels of Radon emanation. Thus, the objective of this study is the environmental monitoring of Radon levels in environments of the Federal University of Pampa in the city of Caçapava do Sul – Rio Grande do Sul, as well as in the environmental compartments of the water. For this, we used the Radon Eye equipment and made measurements for at least 24 hours in each environment of the Prof. Daniela de Rosso Tolfo buildings, Center for Environmental Science and Technology building and the Mining, Planning and Ore Treatment building, in addition to measuring the radon level in the campus wetland surface water. The results showed daily average levels ranging from 13.00 to 142.29 Bq/m³, with daily peaks ranging from 24.00 to 230.00 Bq/m³, with some rooms/laboratories having levels above the maximum level recommended by the European Union, of 140.00 Bq/m³. There are still no safe levels of exposure to Radon according to the literature, and concentrations of 50 Bq/m³ are related to the highest incidence of lung cancer and leukemia in chronic exposures. The water sample collected in the flooded area of the campus showed a concentration of 1.658 Bq/L, remaining within the parameters related to some works in the literature, but still presenting a worrying result. Therefore, this work concludes that Rn²²² levels on campus present potential health risk, particularly in ground floor environments and for employees who frequent the spaces for many hours a day, and adequacy measures are suggested that can be simple and effective. low cost, such as the act of opening the door of an enclosed space and letting the air in for a few minutes before staying in that place for a longer time, to increase the aeration of these spaces and reduce occupational risk.